2020
DOI: 10.3390/v12010097
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis B Virus Infection Associated with Increased Colorectal Cancer Risk in Taiwanese Population

Abstract: Chronic hepatitis B virus (HBV) infections and colorectal cancer (CRC) are prevalent in Taiwan. We carried out a population-based case-control study to assess the association between HBV infection and CRC risk. Using the National Health Insurance Research Database of Taiwan, we identified 69,478 newly diagnosed patients with CRC from 2005 to 2011. We further randomly selected 69,478 age- and gender-matched controls without CRC from the same database. Odds ratios (ORs) were calculated to evaluate the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“…Chronic liver disease and cirrhosis are the ninth leading causes of death; and liver cancer is the second leading causes of cancer death in Taiwan. [ 2 ] The main causes of chronic liver disease, cirrhosis and liver cancer in Taiwanese are viral hepatitis B (70%) and C (20%). For hepatitis B surface antigen bearing carriers with active hepatitis; about 15 to 20% of them develop cirrhosis with higher incidence of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic liver disease and cirrhosis are the ninth leading causes of death; and liver cancer is the second leading causes of cancer death in Taiwan. [ 2 ] The main causes of chronic liver disease, cirrhosis and liver cancer in Taiwanese are viral hepatitis B (70%) and C (20%). For hepatitis B surface antigen bearing carriers with active hepatitis; about 15 to 20% of them develop cirrhosis with higher incidence of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The insurance program covers nearly 99% of the Taiwanese citizens ( 22 ). Detailed information of the program is available in our previous studies ( 23 , 24 ). This research was approved by the Institutional Review Board of China Medical University and Hospital Research Ethics Committee (Institutional Review Board approval number: CMU-REC-101-012).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the association between HBV infection and CRC was also strongly pointed out. Indeed, HBV infection was significantly associated with the risk of CRC in a cohort of Taiwanese subjects [108] . This study confirmed what was previously reported by Song and colleagues, who found HBV seropositive patients to display a higher CRC risk by comparison with the HBV negative subjects [109] .…”
Section: Eukaryotic Viruses and Their Contribution To Carcinogenesis:mentioning
confidence: 99%